ANTIMALARIALACTIVITY OF Cleome viscosa EXTRACT (INVITRO PLASMODIUM FALCIPARUM CHLOROQUIN RESISTANT GROWTH INHIBITON) - Antika, Sindi; Ekawanti, Ardiana; AH, Tetrawindu (Faculty of Medicine Universitas Mataram, 2013)
Background. Malaria is public health problem all over the world as WHO data was 300-500 million people were infected and of 2.7 million were dead annually. The main problems to eradicated malaria was resistance of parasite against convensional antimalaria. Thus, the new potential antimalaria substances need to find out. The Cleome viscosa was empirically used by inhabitant in Lombok to cure signs as malaria shown. Objective. The objective of this study was to explore the effectiveness of Cleome viscosa as antimalaria substance by experimentally study against isolat of P. falciparum chloroquin resistance strain. Method. This study design was experimental laboratory design. The Cleome viscosa extract was exposed to P. falciparum chloroquin resistance isolate. Dosage used in this research were 5µg/ml, 10 µg/ml, 25 µg/ml, 50 µg/ml, 75 µg/ml and 100 µg/ml. Control groups were control positive group that the P. falciparum exposed to chloroquin and control negative group no substances added. Parasitemia level and parasitic inhibition counted based on infected erythrocyte of 5000 eryhrocyte count in thin smear. Result. In the lowest dose group (5 µg/ml) shown 67 % parasitic inhibition, the highest parasitic inhibition was in the dose group 10 µg/ml up to 82 %. All dose group was significantly different from control groups (p